Effect of ultrasound-microwave and microwave-ultrasound treatment on physicochemical properties of corn starch - Yilmaz, Aslihan; Tugrul, Nurcan (ELSEVIER, 2023)
Natural starch is an agricultural sourced biopolymer being low cost, biodegradable, high efficiently, renewable and easy available. Despite these advantages, phisochemical properties of native starch are limited for most industrial applications and must be modified. Ultrasound and microwave treatment have been widely applied separately for starch modification. Ultrasound treatment, with high efficiency and low cost, and microwave treatment, which produces homogeneous and high quality products, are short proceesing time technologies that can be used together to change the structure and properties of starches obtained from various plants. In this study the effects of ultrasound and microwave combined treatment on the physicochemical properties of natural corn starch were investigated. Corn starch was irritated using different combination of ultrasound-microwave and microwave-ultrasound treatment; using 90, 180, 360 and 600 W microwave power during 1, 2, 3 min, and using ultrasound at 35 degrees C constant temperature for 20, 30, 40 min. The structural changes of modified corn starches were determined by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) analyses. Nowadays, many physical methods are used for starch modification, but limited studies were on ultrasound-microwave and microwave-ultrasound combined treatment method. As a result of this study, it was observed that ultrasound and microwave combination is an efficient, fast and environmentally friendly method for natural corn starch modification.
Keywords: Corn; Starch; Modification; Ultrasound; Microwave; DUAL MODIFICATION; MORPHOLOGY; CASSAVA; IMPACT; Acoustics; Chemistry